Situation Report: Romania, 13 June 1975 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Resistance in the Realm of Fine Arts? College Graduates Assigned to Jobs in Production Mild Soviet Response to Criticism of Comecon Hungarian Planning Chief Visits Romania Military Relations with Bulgaria in Power Generation and Oil Prospecting Ceausescu's Latin American Tour: Brazil, Venezuela, and Mexico Ceausescu's Counselor Loses Second Function